Gerenciamento dos processos judiciais: estudo comparado dos poderes e atuação do juiz na Inglaterra, nos Estados Unidos e no Brasil - Thiago Carlos de Souza Brito (2013)
The crisis faced by the Brazilian judiciary system indicates the need of improvement on trial. The lack of technics of judicial case management by Brazilian judges can cause a delay of judgment. There is no concern with the rationalization of informal procedures used, generating widespread inefficiency. Thus, the present work aims to study within comparative law, the application of the judicial case management on court proceedings in the countries which adopt the common law system, specifically the United States and England. Then there will be the examination of the application of management techniques of lawsuits in the judiciary, in accordance with the procedural rules then prevailing.